Nonmetastatic castration-resistant prostate cancer: Novel agents to treat a lethal disease - Henriquez, Ivan (World J Clin Oncol, 2021)
Nonmetastatic castration-resistant prostate cancer (nmCRPC) - defined as prostate-specific antigen (PSA) > 2 ng/mL, testosterone castration levels < 1.7 nm/L, and the absence of metastatic lesions on conventional imaging (computed tomography or bone scan) - has been defined as a lethal disease by the Prostate Cancer Work Group. One-third of patients with prostate cancer who receive androgen deprivation therapy for biochemical recurrence after local treatment will develop CRPC, with death occurring an average of 2.5 years after diagnosis of castration resistance. Most patients diagnosed with nmCRPC are asymptomatic or minimally symptomatic at diagnosis due to local treatment. In patients with short PSA doubling times (< 10 mo) and high baseline PSA levels, there is a high risk of bone metastases followed by prostate cancer-related mortality. These patients also present significant morbidity that negatively impacts quality of life (QoL). Recently, the results of three randomized trials (PROSPER, SPARTAN, and ARAMIS) were published. Those trials evaluated the efficacy of three different androgen receptor inhibitors - enzalutamide, apalutamide, and darolutamide - in patients with nmCRPC. In all three trials, the study drugs improved both metastasis-free survival and overall survival compared to placebo, plus on-going androgen deprivation therapy without a negative impact on QoL. In patients with nmCRPC, the most important clinical objective is early detection and treatment to maintain a low tumor burden and to prolong the symptom-free interval. For patients with nmCRPC, these novel drugs offer new hope for better QoL and survival outcomes.